High-stability CsPbIBr2 nanocrystal with nitrogen-doped graphene quantum dot/titanium dioxide for enhancing rhodamine B photocatalytic degradation under visible light. Issue 3 (June 2022) - Chen, Bo-Chun; Liao, Wan-Hsuan; Wu, Chia-Ching
Abstract: All-inorganic CsPbX3 perovskite quantum dots have attracted substantial research interest because of their great potential for application on the photoelectronic materials. However, CsPbX3 is sensitive to polar substances and thermal treatment, both of which severely degrade the photoluminescence (PL) properties. In this study, highly stable CsPbIBr2 nanocrystals with nitrogen-doped graphene quantum dots (N-GQD-CsPbIBr2 nanocrystals) were successfully synthesized. The nanocrystals exhibit excellent thermal stability and high chemical stability in a polar environment. Titanium dioxide (TiO2 ) was combined with N-GQD-CsPbIBr2 nanocrystals to obtain a N-GQD-CsPbIBr2 /TiO2 nanocomposite. Photocatalytic activity was assessed by testing the rate of rhodamine B (RhB) degradation under visible-light irradiation. The N-GQD-CsPbIBr2 /TiO2 nanocomposite exhibited more efficient RhB degradation after 1 h (90% efficiency) than the N-GQDs, TiO2, the N-GQD-CsPbIBr2 nanocrystals, and the N-GQD/TiO2 nanocomposite. The degradation efficiency of the N-GQDs, TiO2, the N-GQD-CsPbIBr2 nanocrystals after 1 h of approximately 2%, 5%, 3%, and 45% respectively. This enhanced photodegradation was attributed to electron and hole transport in opposite directions at the junction of the N-GQD-CsPbIBr2 /TiO2 nanocomposite and reduced recombination of charge carriers, which enable the rapid generation of active species ( OH radicals and O2 − ions). Graphical Abstract: ga1 Highlights: The N-GQDs-CsPbIBr2 nanocrystals were prepared with N-GQDs being used as the ligand. The highly stable N-GQDs-CsPbIBr2 nanocrystal in different temperature and in polar solvents is obtained. 90% of RhB was photo degraded using GQDs-CsPbIBr2 /TiO2 nanocomposites after visible light irradiation for 1 h. The reaction rate constant of GQDs-CsPbIBr2 /TiO2 nanocomposites was 20 times better than that of TiO2 . GQDs-CsPbIBr2 /TiO nanocomposites is found to be efficient and stable for several repeated cycles.